CLINICAL EXPERIENCE OF TRIPLE-NEGATIVE BREAST CANCER TREATMENT - Djakhongir R. Sabirov; Petr Y. Ignatov; Oybarchin J. Yusupova (Central Asian Journal of Medicine, 2022)
The authors have demonstrated a successful case of treating a patient by using an optimized approach to immunological correction in the course of oncolytic therapy. Treatment began with the correction of the immune system using nonspecific immunomodulatory agents and methods. Afterwards, a course of oncolytic therapy (chemotherapy) was carried out, and at first full doses of cytostatic drugs were used, and then their dosages were lowered. At the end of the course of chemotherapy, it is recommended to use drugs that suppress the processes of proliferative reactivation of tumor cells. The authors believe that the description of this clinical experience may be interesting in terms of searching for new approaches to the management of cancer patients.